Sex-specific maternal calcium requirements for the prevention of nonalcoholic fatty liver disease by altering the intestinal microbiota and lipid metabolism in the high-fat-diet-fed offspring mice. (1st November 2020) - Li, Ping; Yan, Kesong; Chang, Xuelian; Chen, Xiaoyu; Wang, Rui; Fan, Xiuqin; Tang, Tiantian; Zhan, Dawei; Qi, Kemin
ABSTRACT: The significance of maternal appropriate calcium intakes for energy metabolism in the offspring has been recognized. Nonalcoholic fatty liver disease (NAFLD) is considered as the hepatic manifestation of metabolic syndrome. So in this study, we proposed that there were long-term effects of maternal calcium status on the progress of NAFLD by altering the intestinal microbiota and lipid metabolism with attention to potential sex differences among the mouse offspring. Thirty-four-week female C57BL/6 J mice were subjected to obtain low, normal and high calcium reproductive diets throughout the gestation and lactation. After weaning, both the male and female mouse offspring were fed with the high-fat diet for 16 weeks, with the normal diet as control. Biochemical indicators in the plasma and hepatic tissue were measured using ELISA or enzymatic methods. The expression of lipid metabolism, inflammatory and fibrosis related genes was determined by RT-PCR. The intestinal microbiota was analyzed by 16S rRNA high-throughput sequencing. Maternal normal and low calcium intake could, respectively, inhibit the progress of high-fat diet induced NAFLD in the male and female mouse offspring, which was characterized by the least lipid droplets, inflammatory infiltration and fibrosis, the lowest concentrations of free fatty acids and triglyceridethe lowest expression of genes involving in de novo lipogenesis and the highest expression of genes related to lipid oxidation and  hydrolysis, inflammatory, and fibrosis. Pyrosequencing of 16S rRNA genes revealed that the male mouse offspring with maternal normal calcium intake and the female mouse offspring with maternal low calcium intake, after the high-fat diet feeding, had distinct intestinal microbiota, which was closer to thosein mice with the normal diet feeding. Analysis of the functional features for the different microbiota was compatible with the expression of genes associated with lipogenesis, lipid oxidation and hydrolysis. Thus, there is a sex-specific manner for maternal calcium requirement to inhibit the progress of offspring NAFLD, that might be less for the female offspring and more for the male offspring.